Iron biofortified rice improves the iron stores of non-anemic Filipino women - Haas, Jere D.; Beard, John L.; Murray-Kolb, Laura E.; del Mundo, Angelita M.; Felix, Angelina; Gregorio, Glenn B. (International Food Policy Research Institute, 2005)
Iron deficiency is the most prevalent nutritional deficiency in the world affecting an estimated 3.5 billion people. Among the most at risk in developing countries, are women of reproductive age. Strategies to alleviate the problem are public education to improve diets, supplementation, and iron fortification of the food supply. Biofortification of staple food crops is a new approach to complement existing interventions. Developing staple food crops with substantial amounts of micronutrients such as iron, zinc, and pro‐vitamin A through conventional breeding and biotechnology has the potential to significantly improve nutritional status of vulnerable groups. In processed and cooked form, biofortified high iron rice developed through conventional breeding at the International Rice Research Institute has four to five times more iron than commercially available rice. Sensory evaluation prior to the feeding study showed that high‐iron rice was comparable with the commercial rice.